2013
DOI: 10.1007/s10147-013-0542-9
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor-2 expression in primary and metastatic gastric cancer

Abstract: HER-2 was significantly overexpressed in gastric cancer versus normal tissue and correlated with VEGF expression. HER-2 in tumor or lymph nodes was an independent negative prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Additionally, it has been reported that miR-7 and miR-331-3p are direct mediators of ERBB2 [23]. It was also reported that ERBB2 is highly expressed in GC tissues and is an independent negative prognostic factor for cancers [10], which is consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, it has been reported that miR-7 and miR-331-3p are direct mediators of ERBB2 [23]. It was also reported that ERBB2 is highly expressed in GC tissues and is an independent negative prognostic factor for cancers [10], which is consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…miR-495 regulates human epidermal growth factor receptor 2 (ERBB2) by binding to the 3′-untranslated regions (3′UTR) in connection with the target prediction program, microRNA.org. ERBB2, an oncogenic agent located in chromosome 17 (17q12–q21), encodes a 185-kDa transmembrane tyrosine kinase receptor (p185) [10]. ERBB2 has been identified to be implicated in cancerous initiation and progression, and its overexpression or amplification served as an independent prognostic factor in GC [11].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence supports the central role of angiogenesis in GC development and progression but few data regarding the role of MCs in GC angiogenesis have been published [34,35,36]. In particular, in a study performed by Mukherjee et al [37], the authors studied MCs density in tissue from patients with gastric ulcers and in tissue from GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the eligible studies that did conduct ISH, the HER2 overexpression/gene amplification rates ranged from 2.0% to 18.3%, with an overall rate of 6.5% (3,11,14,16). In the present meta-analysis, HER2 IHC overexpression was not correlated with poor prognosis (HR 0.960, 95% CI 0.776-1.188) as in gastric cancer (22,23). However, CRC with HER2 IHC overexpression showed higher rates of lymph node and distant metastasis than CRC without HER2 IHC overexpression.…”
Section: Discussionmentioning
confidence: 51%